LAND COVER CHANGE ANALYSIS IN TERONG TAWAH USING GOOGLE EARTH ENGINE - Muhammad Adriyansyah; Fitrah Ramadhan; Dimas Indrawardi; Nuzla Af'idatur Robbaniyyah; Kurnia Ulfa; Muhammad Rijal Alfian (Fraction: Jurnal Teori dan Terapan Matematika, 2026)
This study analyzes land cover changes in Terong Tawah Village, West Lombok using Google Earth Engine (GEE) as the main platform. Landsat 8 satellite imagery data for 2015, 2018, 2022, and 2023 was used to classify five types of land cover: forests, settlements, fields, vacant land, and roads. The methods applied include data preprocessing, classification using the Random Forest algorithm, and spatial change analysis. The results show significant trends, such as an increase in settlement area and a decrease in vegetation. Validation of classification accuracy results in an overall accuracy value of above 93% per year. This study demonstrates the effectiveness and accuracy of GEE in analyzing land cover changes and provides important insights into development dynamics in Terong Tawah Village.